2015
DOI: 10.1016/j.colsurfb.2015.02.020
|View full text |Cite
|
Sign up to set email alerts
|

AFM in peak force mode applied to worn siloxane-hydrogel contact lenses

Abstract: The objective of this work is to apply Atomic Force Microscopy in Peak Force mode to obtain topographic characteristics (mean roughness, root-mean-square roughness, skewness, kurtosis) and mechanical characteristics (adhesion, elastic modulus) of HighlightsThe Peak Force mode of AFM provides topographic and mechanical properties.The worn CLs show significant changes in respect to the un-worn CLs.The AFM results can be correlated with clinical test results.The elastic modulus is not the only parameter to consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Abadias et al [24] applied the AFM in peak-force mode to obtain topographic and mechanical characteristics of Siloxane-Hydrogel soft contact lenses. The study was carried out in liquid using cantilevers of silicon nitride of low spring constant (0.1−1N/m) and of natural frequency in liquid between 2 and 20 kHz.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Abadias et al [24] applied the AFM in peak-force mode to obtain topographic and mechanical characteristics of Siloxane-Hydrogel soft contact lenses. The study was carried out in liquid using cantilevers of silicon nitride of low spring constant (0.1−1N/m) and of natural frequency in liquid between 2 and 20 kHz.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…16,[22][23][24] Over the last ten years, the need to lower the limits of spatial detection for addressing the biomolecular processes that control cells response to changes of neighboring environments, has given rise to the development of faster and more accurate force curve measurement technologies, in particular the Peak-Force AFM tapping mode (Bruker technology). 25,26 This mode of force curves acquisition allows a precise control of the sample to AFM probe interactions and a high resolution (nanometer scale) for AFM surface imaging. Methodologies differ according to e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigating interactions between hydrogel contact lenses and the cornea found significant alterations in the surface morphologies of hydrogel contact lenses during use without any eye‐drop medication . The ocular environment itself in general could be prone to create discomfort or pain, and the problems experienced might not be attributed to the usage of eye‐drops alone.…”
Section: Discussionmentioning
confidence: 99%